Analysis of performance determinants of microfinance institutions and factors affecting their performance: A case of Harare microfinance institutions - Matare, Edson Decide (Midlands State University, 2020)
Microfinance main objective is to reduce poverty, to achieve this amazing objective microfinance institutions have to become strong in financial performance because donor dependency is uncertain. The research aim was to analyse the performance determinants of microfinance institutions and factors affecting their performance. This study was conducted focusing microfinance institutions in Harare. The main objective is to determine performance of microfinance institutions in Zimbabwe. The issue of sustainability so as to outreach to the marginally poor and those in rural areas has brought in two aspects which need to be balanced thus the social performance and financial performance. Microfinance institution must be able to cover up all operating costs at the same time reaching to the poor thus the determinants of financial performance is crucial as it enhance decision making by management. A descriptive research design was adopted as it enables to gather both qualitative data. Total population constitute of 40 operations managers and 10 accountants giving a total of 50. The sample size has 37 operations managers and 8 accountants. Judgemental sampling was employed as it allows getting information from those who have knowledge in performance of institutions. Mode was applied on questionnaires and thematic approach was used on interviews as data analysis approach. The information was gathered in the form of primary data. Structured questionnaires in the form of likert scale and interview questions were used to collect data from the respondents. The research findings were presented in the form of graphs and tables. It was established that to achieve sustainability and profitability, managers and policy makers must know the major elements which affect the financial performance namely: portfolio quality, capital asset ratio, gearing ratio, operational efficiency, size of MFIs, age of MFIs, market concentration and real GDP and factors affecting microfinance institution which are policy factors, geographic variables and institutional variables. It was recommended that since inefficiency is a major challenge of microfinance institution in Zimbabwe, management should come up with good cost management policy in the form of reducing operating expenses and credit risk management through information communication technology and mobile banking. Microfinance institutions should follow retail banking practices by implementing a robust financial management system and good managerial governance so as to preserve profitability as well as sustainability